Metagenomic data-mining reveals enrichment of trimethylamine-N-oxide synthesis in gut microbiome in atrial fibrillation patients - Zuo, Kun; Liu, Xiaoqing; Wang, Pan; Jiao, Jie; Han, Chunming; Liu, Zheng; Yin, Xiandong; Li, Jing; Yang, Xinchun (BMC genomics, 2020)
Background The gut bacteria-derived metabolite trimethylamine-N-oxide (TMAO) has been discussed in various cardiometabolic diseases. However, evidence characterizing the microbial population responsible for TMAO accumulation in patients with atrial fibrillation (AF), an increasingly prevalent arrhythmia, is yet lacking. In order to understand the key gut microorganisms that produce TMAO in AF, trimethylamine (TMA)-synthesis enzymes and metabolic pathways, as well as the potential TMA-producers in gut microbiome were assessed based on metagenomic data-mining in a northern Chinese cohort consisting of 50 non-AF controls and 50 patients with different types of AF. Results Compared to the control subjects, AF patients showed a marked increase in the microbial genes underlying TMA formation in the gut, which included 12 potential TMA-synthesis functional orthologs and 1 module. The specific bacterial genes, including choline-TMA lyase , carnitine monooxygenase , glycine betaine reductase , and TMAO reductase , were elevated in the gut of AF patients. Furthermore, 16 genera were assigned and significantly correlated with TMA-enzymatic genes, where 9 genera were remarkably enriched in the gut communities of AF patients. Neither of these TMA-synthesis pathways nor the microbial players showed a significant discrepancy between different types of AF in the current cohort. These gut microbes might participate in the formation of TMA by activating the key TMA-synthesis enzymes and contributing to the functional pathways in AF patients. Conclusions The present study provides an in-depth insight into the potential bacteria and metabolic pathways involved in TMA production in the gut of AF patients. These findings emphasize a key role of the gut bacteria in driving TMAO formation during AF pathogenesis, thereby indicating its therapeutic potential as an intervention strategy of AF by targeting TMA-synthesis pathways and dysbiotic gut microbiota.